1. Question:` a^4 - 27a^2 + 1` 

    Answer
    `a^4 - 27a^2 + 1 = (a^2)^2 - 2.a^2.1 + (1)^2 - 25a^2`
    
              ` = (a^2 - 1)^2 - (5a)^2`
    
               `= {(a^2 - 1) + 5a} {(a^2 - 1) - 5a}`
    
               `= (a^2 + 5a - 1) (a^2 - 5a - 1)`  (Ans)






    1. Report
  2. Question:উৎপাদকে বিশ্লেষণ কর: `x^4 - 6x^2y^2 + y^4` 

    Answer
    `x^4 - 6x^2y^2 + y^4 = (x^2)^2 - 2x^2y^2 + (y^2)^2 - 4x^2y^2`
    
             `= (x^2 - y^2)^2 - (2xy)^2`
    
             `= (x^2 - y^2 + 2xy) (x^2 - y^2 - 2xy)`
    
             `= (x^2 + 2xy - y^2) (x^2 - 2xy - y^2)`






    1. Report
  3. Question:উৎপাদকে বিশ্লেষণ কর: `(a^2 - b^2) (x^2 - y^2) + 4abxy` 

    Answer
    `a^2 - b^2) (x^2 - y^2) + 4abxy`
    
     `= a^2x^2 - a^2y^2 - b^2x^2 + b^2y^2 + 4abxy`
     
     `= a^2x^2 + 2axby + b^2y^2 - a^2y^2 + 2axby - b^2x^2`
    
     `= (a^2x^2 + 2abxy + b^2y^2) - (a^2y^2 - 2abxy + b^2x^2)`
    
     `= {(ax)^2 + 2ax.by + (by)^2} - {(ay)^2 - 2.ay.bx + (bx)^2}`
    
     `= (ax + by)^2 - (ay - bx)^2`
    
     `= {(ax + by) + (ay - bx)} {(ax + by) - (ay - bx)}`
    
     `= (ax + by + ay - bx)^2`
    
     `= {(ax + by) + (ay - bx)}{(ax + by) - (ay - bx)}`
    
     `= (ax + by + ay - bc) (ax + by - ay + bx)`  (Ans)






    1. Report
  4. Question:উৎপাদকে বিশ্লেষণ কর: `4a^2 - 12ab + 9b^2 - 4c^2` 

    Answer
    `4a^2 - 12ab + 9b^2 -4c^2`
    
     `= (2a)^2 - 2.2a.3b + (3b)^2 - 4c^2`
    
     `= (2a - 3b)^2 - (2c)^2`
    
     `= (2a - 3b + 2c) (2a - 3b - 2c)`   (Ans)






    1. Report
  5. Question:উৎপাদকে বিশ্লেষণ কর: `9x^4 - 45a^2x^2 + 36a^4` 

    Answer
    `9x^4 - 45a^2x^2 + 36a^4`
    
     `= 9(x^4 - 5a^2x^2 + 4a^2)`
    
     `= 9(x^4 - 4a^2x^2 - a^2x^2 + 4a^4)`
    
     `= 9{x^2(x^2 - 4a^2) - a^2(x^2 - 4a^2)}`
    
     `= 9(x^2 - a^2) (x^2 - 4a^2)`
    
     `= 9(x^2 - a^2){x^2 - (2a)^2}`
    
     `= 9(x + a) (x - a) (x + 2a) (x - 2a)`  (Ans)






    1. Report
Copyright © 2025. Powered by Intellect Software Ltd